Preweaning grouth traits in calves dual purpose system in the municypality of Arauca (2023)
Data from pre-weaning growth of crossbred calves, born during the years 2009 and 2010 was anlyzed. Three growth traits: birth weight (BW, n = 70), weaning weight adjusted to 270 days of age (PD, n = 69) and daily weight gains between birth and weaning (GDP, n = 69) were considered using General Linear Models (GLM) of SAS statistical package. Comparison of means was done by Tukey test. The estimated mean was 28,92 ± 3,2 Kg., 137,65 ± 28,04 Kg., and 362,3 ± 86,96 g/d for the PN, PD and GDP, respectively. A variation coefficient of 6,82, 15,85 and 21,60% was found for the same characteristics. The farm was a significant factor of variation in growth traits BW and WW (P<0,01) and GDP at the 5% statistical probability (P<0,05). The sex of calf affected (P<0,05) BW and PD and was not significant for GDP (P>0,05). The year of birth of the offspring had a significant effect (P<0,05) on the PN and had no effect on PD and GDP (P>0,05). The breeding race in farm did not affect (P>0,05) the birth weight and weaning had no effect (P<0,05) on GDP. We conclude that environmental factors analyzed: farm, year of birth and sex of calf and the effect of racial group affected preweaning growth parameters studied.